HATE SPEECH IN INDONESIA: A FORENSIC LINGUISTICS - Sofia Idawati Lubis; Yunita Mutiara Harahap; Wiki Tedi Rahmawati; Chyntia Febiola (EXCELLENCE: Journal of English and English Education, 2023)
This study intends to examine the scientific article about the phenomenon of hate speech in pandemic era in Indonesia from forensic linguistics view. By using a meta-analysis technique on Google Schoolar, an official website intended as a collection of scientific articles in Indonesia. A total of 150 articles were accessed from Google Scholar. To assure the review's focus, a selection process for inclusion and exclusion criteria was carried out before it began. There are 20 eligible articles to be reviewed. Findings showed that most of the researchers used social media as the source of data, most of the researchers used the theory of speech act to analyse the data.